Pengaruh Motivasi Belajar terhadap Performa Mahasiswa Pasca Pandemi COVID-19 - Diva Ratna Kumala Ardellia; Aryo Pinandito; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Student performance in post-pandemic conditions of COVID-19 is certainly different from online conditions during the COVID-19 pandemic. There are many factors that can improve student performance. Learning during this transitional period has been implemented by Universitas Brawijaya in the odd semester of 2022 which applies hybrid learning to fully offline learning. With this research aimed at analyzing the direct and indirect effects of learning motivation on student performance in post-pandemic condition of COVID-19 as measured based on comparisons of their experiences with online conditions during the COVID-19 pandemic using quantitative methods. Respondent data received in this study were 122 active students of the Information Systems study program at Brawijaya University starting from the class of 2017 to the class of 2022. The results of the analysis prove that there is no direct effect of learning motivation on student performance in post-pandemic conditions of COVID-19. But there is an indirect effect between learning motivation on student performance through the Community of Inquiry (CoI) framework. The Community of Inquiry (CoI) framework consists of Social Presence, Cognitive Presence, and Teaching Presence. This indirect effect analysis give a results that Cognitive Presence and Teaching Presence can mediate the effect of learning motivation on student performance. Meanwhile, Social Presence yielded results that could not mediate the effect of learning motivation on student performance.